Characteristics Of Preparing Students Of Pedagogical Education For Creative Activity - Usmonaliyev Ikromjon Murodjon o‘gli; Abdullayeva Nozimaxon Erkinovna (Euro Asian Journal Publishing, 2024)
This article presents some thoughts on the concept of creativity, its innateness in a person, the positive impact of creativity on the educational process, its study by scientists, and the specificity of preparing students of pedagogical education for creative activity.
Keywords: Creativity; pedagogical process; result; development